STRATEGI KOMUNIKASI PENINGKATAN ENGAGEMENT (LIKE, SHARE, DAN COMMENT) TIKTOK @UNIVERSITAS DIPONEGORO DAN INSTAGRAM @UNDIP.OFFICIAL MELALUI PRODUKSI KONTEN VIDEO SEBAGAI PROJECT COORDINATOR DAN CONTENT PLANNER - Estya Rastra Pratidina; Joyo Nur Suryanto Gono (Interaksi Online, 2026)
(UNDIP) has proactively adopted digital communication channels as a strategicinstrument to strengthen its institutional reputation. As a higher education institution targetingGeneration Z, UNDIP faces challenges in building effective interaction on social media,particularly on the TikTok platform. Content that tends to be formal and one-way is often lesseffective in attracting young audiences who prefer a humanistic, inclusive, and interactivenarrative approach. This professional project aims to design and implement a communicationstrategy through the "Jejak UNDIP" program to increase engagement (such as likes, shares,and comments) on the @undip.official TikTok account. Through planned video contentproduction, this project focuses on content pillars that highlight the humanistic side of thecampus, facilities such as Electric Buggies through the Smart & Eco Campus campaign, andstudent achievements. The implementation results show that the shift in communication stylefrom formal-segmentative to a more interactive approach has proven effective in attractingactive audience engagement. This increase in engagement not only expands the reach ofinformation but also strengthens UNDIP's image as an adaptive and modern university in theeyes of Generation Z.